Business Resilience in the Digital Transformation Era - Haedar Akib; Nuril Furkan; Sumarno Sumarno; Ahmad Budidarma; Rudi Salam; Syamsul Hadi (Universitas Negeri Makassar, 2022)
During and after the pandemic, digital transformation is the driving force behind organizations' business resilience. In addition, continuous innovation should be encouraged. Business resilience is a firm's capacity to forecast, plan, respond and adapt to change in order to survive. Business resilience must be supported by digital transformation, one of the breakthroughs that can jump-start an entire organization. The interrelated factors include dynamic capabilities, technological capabilities, agile leadership, innovative ambidexterity, and knowledge stock.